(untitled) (International Journal of Current Engineering and Technology, 2014)
This paper discusses the model of a Job Traffic Queue of a cloud based research collaboration platform. The objective is to compute the size of those queues, the time that jobs spend in them i.e. number of simultaneous HTTP GET file requests handled by the server, and the total time required to service a request. This system captures efficiency in service time, server utilization, queuing response times, queuing workload and contents for a Cloud based Research Collaboration platform. MATLAB Simevent tool 2009b was used to develop the cloud queuing model. The proposed Queuing-Model-Based Adaptive Control approach combines both the modelling power of queuing theory and self-tuning power of adaptive control. Therefore, it can handle both modelling inaccuracies and load disturbances in a better way.